Immediate And Long Term Effects Of Percutaneous Mitral Balloon Valvuloplasty On Atrial Conduction Velocities In Patients With Mitral Stenosis - Agus, Hicaz Zencirkiran (J Atr Fibrillation, 2019)
BACKGROUND: P-wave dispersion (PWD) is an electrocardiographic (ECG) marker of nonuniform and heterogeneous atrial conduction with ECG leads of different orientation. The aim of our study was to investigate the immediate and long term effects of successful percutaneous mitral balloon valvuloplasty (PMBV) on PWD in severe rheumatic MS patients and to analyse the restenosis, atrial fibrillation (AF) and redo balloon valvuloplasty rate. METHODS: We enrolled 41 consecutive MS patients with sinus rhythm who underwent PMBV. A 12-lead ECG and transthoracic echocardiography were performed for each patient one day before, within 72 hours after the procedure and followed up by clinical visit at a mean of 5,57±1,46 (3-8) year.The mean patient age was 44.1±10.86 years. RESULTS: Pmax 1(pre PMBV) and PWD 1(pre PMBV) decreased 1-3 days after PMBV. MVA improved immediately after the procedure; but lately the mean MVA decreased significantly indicating the initiation of restenosis. Composite endpoints were associated with LA 1 (p = 0.02), MVA 2 (1-3 days after PMBV) (p= 0.019), mean gradient 2 (p= 0.028), PWD 3 (3 years after PMBV) (p < 0.001) and Pmax 3 (3 years after PMBV) (<0,001). AF incidence was associated with PWD 2 (p=0,019) and PWD 3 (p=0,010). There was 14 composite endpoint on follow up and at multivariate analysis PWD 3 was identified as an independent predictor of the composite endpoint (p=0.048, hazard ratio=1.36, 95% confidence interval (CI): 1,002−1.867). CONCLUSIONS: This study has demonstrated that Pmax and PWD significantly decreased within 3 days after PMBV. Furthermore, long term PWD was associated with AF and identified as an independent predictor of the composite endpoint.